THE CHALLENGES OF COMMUNICATION BETWEEN - Henryk, NOGA (Trends in education, 2012)
Nowadays outsourcing has become an inseparable element of the existence of all the huge corporations. It is becoming more and more popular with medium and small companies. IT sector is one of the most intensely developing branch of outsourcing. At present no company can exist if it does not possess information infrastructure and advanced technological systems. Information outsourcing, that is transferring all the issues not directly connected with a given company business, is the solution.
Keywords: outsourcing; computerization; information technology.